2023
DOI: 10.15585/mmwr.su7201a9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Physical Activity Behaviors in 2021 and Changes from 2019 to 2021 Among High School Students — Youth Risk Behavior Survey, United States, 2021

Abstract: The fall of 2021 was the first school semester to begin with widespread in-person learning since the COVID-19 pandemic began. Understanding dietary and physical activity behaviors of adolescents during this time can provide insight into potential health equity gaps and programmatic needs in schools and communities. This report uses data from the 2021 national Youth Risk Behavior Survey conducted among a nationally representative sample of U.S. public and private school students in grades 9–12 to update estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this study, the overall prevalence of meeting MSE recommendations was 34.6%, much lower than in other studies performed in high-income countries and a previous study conducted in China. For instance, one nationally representative survey conducted in 2021 among 17,232 US students reported that 44.9% of high school students exercised ≥3 days/week to strengthen or tone their muscles [ 10 ]. Another study conducted in 2013 and 2014 of 35,297 grade 9-12 Canadian students reported that 53.7% of students performed MSE ≥3 days per week [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the overall prevalence of meeting MSE recommendations was 34.6%, much lower than in other studies performed in high-income countries and a previous study conducted in China. For instance, one nationally representative survey conducted in 2021 among 17,232 US students reported that 44.9% of high school students exercised ≥3 days/week to strengthen or tone their muscles [ 10 ]. Another study conducted in 2013 and 2014 of 35,297 grade 9-12 Canadian students reported that 53.7% of students performed MSE ≥3 days per week [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of engaging in MSE was evaluated through the question “During the past 7 days, on how many days did you do exercises to strengthen or tone your muscles, such as push-ups, sit-ups, or weight lifting?” Response options included “none,” “1 day,” “2 days,” “3 days,” “4 days,” “5 days,” “6 days,” and “7 days.” This item, with an acceptable reliability for children and adolescents (κ coefficient >0.55) [ 36 ], has been widely used for health behavior surveillance worldwide [ 10 , 11 ]. Meeting MSE recommendations was defined as engaging in MSE at least 3 days in the past 7 days, which is in accordance with World Health Organization (WHO) guidelines [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access drink 100% fruit juice <1 time/day and 14.7% drink sugar-sweetened soda/pop ≥1 time/day. 5 Further augmenting the risk among adolescents, pubertal changes occur in the years immediately preceding high school that can contribute to insulin resistance. 6 This information indicates that health-promoting interventions are needed before high school (ie, ages 10-13 years) so that young adolescents can begin to establish healthy behaviours to reduce their risk for adverse outcomes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Contributing to the obesity problem and increasing the risk for chronic conditions, 76.1% of high school students do not attain the recommended ≥60 minutes/day of physical activity (PA), 75.0% do not eat breakfast daily, 45.3% eat vegetables <1 time/day, 47.1% eat fruit or drink 100% fruit juice <1 time/day and 14.7% drink sugar-sweetened soda/pop ≥1 time/day. 5 Further augmenting the risk among adolescents, pubertal changes occur in the years immediately preceding high school that can contribute to insulin resistance. 6 This information indicates that health-promoting interventions are needed before high school (ie, ages 10–13 years) so that young adolescents can begin to establish healthy behaviours to reduce their risk for adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%